HOW DOES SMILES WORK THROUGH GRASSROOTS TRAINING? A REVIEW STUDY ON CHILDREN'S SOCCER COMMUNITIES - Dina Agustina; Atih Purwaningsih (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. One must follow a gradual and continuous development process so that clear goals can be achieved at each level through grassroots training with SMILES elements that can provide a comfortable space and safe equipment (safe from danger). Children are active throughout the grassroots training. Objectives. The purpose of this article is to determine the success or effectiveness of applying the SMILES elements in children's soccer communities through grassroots training. Method. The search in this study used the Harzing Publish or Perish application. The search began using the Google Scholar database, which is considered one of the citation indexing systems. The search strategy included a combination of keyword variations (“children” OR “kids” AND “football” OR “soccer” AND ‘grassroots’ AND “smiles”). The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Initially, 534 publications were obtained from the identification process through the Google Scholar database search. After applying the exclusion criteria, only 5 articles remained. Results. Based on the results of literature research on various national and international journals and several books on grassroots training by applying the SMILES elements to children's soccer communities. The results indicate that grassroots training conducted using the SMILES elements can support children's soccer communities in mastering good technical and tactical soccer skills, maintaining excellent physical condition, and developing a strong mental attitude. Conclusion. Everyone (the children's football community) is involved regardless of ability or disability. There are goals, development, and challenges to become better, as well as trying new things. Enjoying grassroots training and achieving success according to one's football playing ability.